DESCRIPTION OF MALE AND REDESCRIPTION OF THE FEMALE OF VEPRIUS FULVUS COSCARON, PHILIP & FAIRCHILD, 1979 (DIPTERA: TABANIDAE: PANGONIINI) (Acta Entomológica Chilena, 2022)
The male of Veprius fulvus Coscaron, Philip & Fairchild, 1979 is described and illustrated the female redescribed. Comments about relationships of this species are offered.
Keywords: Neotropical Región, Chile, Tabanidae, Pangoniini